2011
DOI: 10.1002/j.2050-0416.2011.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Environmental Factors During Very High Gravity Brewing Fermentations

Abstract: The impact of the initial dissolved oxygen, fermentation temperature, wort concentration and yeast pitching rate on the major fermentation process responses were evaluated by full factorial design and statistical analysis by JMP 5.01 (SAS software) software. Fermentation trials were carried out in 2L-EBC tall tubes using an industrial lager brewing yeast strain. The yeast viability, ethanol production, apparent extract and real degree of fermentation were monitored. The results obtained demonstrate that very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Moonjai et al emphasized that the lowest growth, as expected, was found under the deaerated conditions. The lack of wort aeration caused a 2‐fold decrease biomass growth in relation to standardized aeration (8 mg O 2 /L).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…Moonjai et al emphasized that the lowest growth, as expected, was found under the deaerated conditions. The lack of wort aeration caused a 2‐fold decrease biomass growth in relation to standardized aeration (8 mg O 2 /L).…”
Section: Resultsmentioning
confidence: 62%
“…Based on the results, they found that a higher air dose led to a visible increase in the number and viability of obtained yeast biomass. Moonjai et al (18) emphasized that the lowest growth, as expected, was found under the deaerated conditions. The lack of wort aeration caused a 2-fold decrease biomass growth in relation to standardized aeration (8 mg O 2 /L).…”
Section: Viable Cell Number and Vitalitymentioning
confidence: 60%
See 3 more Smart Citations